Defining the first preventive conservation guidelines for hand-painted magic lantern glass slides - Santos, Ângela (2021)
This article intends to define and make available guidelines for the preventive conservation of hand-painted glass slides for magic lanterns, the first optical instruments for the projection of images, invented in the 17th century. For this purpose, around 300 handpainted glass slides from the Portuguese Cinematheque – Museum of Cinema (CP) and Nacional Museum of Natural History and Science of the University of Lisbon (MUHNAC), were studied in terms of representativity in these collections, discursive genre, type of construction or movement mechanism, state of preservation and degradation problems. A survey was designed and distributed to institutions across the globe aiming for an overview of the formal characteristics of the collections of magic lantern slides and the preventive and interventive conservation measures undertaken. The guidelines are focused on the environmental conditions (temperature, relative humidity, and light), fine particles and pest control, storage and display conditions and materials, as well as handling. Recommendations on performative projections or demonstrations are also provided.